1) - 3 * ( X - 4 ) = 5X - 12 - 3X + 12 = 5X - 12 5X + 3X = 12 + 12 8X = 24 X = 3 -----------------------------2) ( 16X - 5 ) - ( 3 - 5X ) = 6 16X - 6 - 3 + 5X = 6 21X = 15 X = 15/21 = 5/7 -----------------------------3) 4 * ( 13 - 3X ) - 17 = - 5X 52 - 12X - 17 = - 5X 12X - 5X = 35 7X = 35 X = 5 -------------------------------4) ( 18 - 3X) - ( 4 + 2X ) = 10 18 - 3X - 4 - 2X = 10 14 - 5X = 10 5X = 4 X = 0,8 -------------------------------5) 14 - X = 0,5 * ( 4 - 2X ) + 12 14 - X = 2 - X + 12 14 - X = 14 - X Ответ любые значения переменной Х -------------------------------6) 4Х - 3 * ( 20 - X ) = 10X - 3 *( 11 + X ) 4X - 60 + 3X = 10X - 33 - 3X 7X - 60 ≠ 7X -